Analyzing Wage Differentials by Fields of Study: Evidence from Turkey - Antonio Di Paolo; Aysit Tansel (Institute of Labor Economics (IZA), 2017)
This paper analyzes the drivers of wage differences among college graduates who hold a degree in a different field of study. We focus on Turkey, an emerging country that is characterized by a sustained expansion of higher education. We estimate conditional wage gaps by field of study using OLS regressions. Average differentials are subsequently decomposed into the contribution of observable characteristics (endowment) and unobservable characteristics (returns). To shed light on distributional wage disparities by field of study, we provide estimates along the unconditional wage distribution by means of RIF-Regressions. Finally, we also decompose the contribution of explained and unexplained factors in accounting for wage gaps along the whole distribution. As such, this is the first work providing evidence on distributional wage differences by college major for a developing country. The results indicate the existence of important wage differences by field of study, which are partly accounted by differences in observable characteristics (especially occupation and, to a lesser extent, employment sector). These pay gaps are also heterogeneous over the unconditional distribution of wages, as is the share of wage differentials that can be attributed to differences in observable characteristics across workers with degrees in different fields of study.
Keywords: J31; J24; I23; I26; 330; decomposition; wage differentials; fields of study; unconditional wage distribution; Turkey